Exclusion-Based Capture and Enumeration of CD4+ T Cells from Whole Blood for Low-Resource Settings. (June 2014) - Howard, Alexander L.; Pezzi, Hannah M.; Beebe, David J.; Berry, Scott M.
In developing countries, demand exists for a cost-effective method to evaluate human immunodeficiency virus patients' CD4 + T-helper cell count. The TH (CD4) cell count is the current marker used to identify when an HIV patient has progressed to acquired immunodeficiency syndrome, which results when the immune system can no longer prevent certain opportunistic infections. A system to perform TH count that obviates the use of costly flow cytometry will enable physicians to more closely follow patients' disease progression and response to therapy in areas where such advanced equipment is unavailable. Our system of two serially-operated immiscible phase exclusion-based cell isolations coupled with a rapid fluorescent readout enables exclusion-based isolation and accurate counting of T-helper cells at lower cost and from a smaller volume of blood than previous methods. TH cell isolation via immiscible filtration assisted by surface tension (IFAST) compares well against the established Dynal T4 Quant Kit and is sensitive at CD4 counts representative of immunocompromised patients (less than 200 TH cells per microliter of blood). Our technique retains use of open, simple-to-operate devices that enable IFAST as a high-throughput, automatable sample preparation method, improving throughput over previous low-resource methods.